Management of Phantom Limb Pain through Thalamotomy of the Centro-Median Nucleus - Ramiro A. Pérez de la Torre; Job J. Rodríguez Hernández; Ali Al-Ramadan; Abeer Gharaibeh (MDPI AG, 2021)
Background: Phantom limb syndrome is defined as the perception of intense pain or other sensations that are secondary to a neural lesion in a limb that does not exist. It can be treated using pharmacological and surgical interventions. Most medications are prescribed to improve patients' lives; however, the response rate is low. In this case report, we present a case of phantom limb syndrome in a 42-year-old female with a history of transradial amputation of the left thoracic limb due to an accidental compression one year before. The patient underwent placement of a deep brain stimulator at the ventral posteromedial nucleus (VPM) on the right side and removal secondary to loss of battery. The patient continued to have a burning pain throughout the limb with a sensation of still having the limb, which was subsequently diagnosed as phantom limb syndrome. After a thorough discussion with the patient, a right stereotactic centro-median thalamotomy was offered. An immediate response was reported with a reduction in pain severity on the visual analogue scale (VAS) from a value of 9-10 preoperative to a value of 2 postoperative, with no postoperative complications. Although phantom limb pain is one of the most difficult to treat conditions, centro-median thalamotomy may provide an effective stereotactic treatment procedure with adequate outcomes.